2007
DOI: 10.1111/j.1468-3083.2007.02457.x
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum toxin type‐A for the treatment of inverse psoriasis

Abstract: BoNTA therapy resulted in improvements in subjective patient symptomatology and objective reductions in erythema and maceration in the treated areas according to photographic evidence. Further large-scale methodologically rigorous studies are required to investigate the safety and efficacy of BoNTA in this indication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 15 publications
0
46
0
1
Order By: Relevance
“…4-6 In one study, all 15 patients with a confirmed diagnosis of inverse psoriasis showed improvements in subjective symptoms, and 13 patients showed improvements in erythema extension, intensity, and infiltration. Treatment was well tolerated.…”
Section: Future Developmentsmentioning
confidence: 98%
See 1 more Smart Citation
“…4-6 In one study, all 15 patients with a confirmed diagnosis of inverse psoriasis showed improvements in subjective symptoms, and 13 patients showed improvements in erythema extension, intensity, and infiltration. Treatment was well tolerated.…”
Section: Future Developmentsmentioning
confidence: 98%
“…2 BoNT is also a therapeutic mainstay for other conditions, such as axillary hyperhidrosis, chronic migraine, and neurogenic detrusor over-activity. 3 The range of potential therapeutic uses continues to expand, with recent clinical studies suggesting that BoNT may be effective for some cases of psoriasis, 4-6 acne, 7,8 and lateral patellofemoral overload syndrome, 9 although these are currently investigative clinical studies and BoNT is unlicensed for these indications.…”
mentioning
confidence: 99%
“…21 More resistant cases, like the one described herein, may require combination therapy. Other therapeutic options include botulinum toxin 22,23 and efalizumab, 24 although evidence of their effectiveness is limited to case reports.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the clinical observation that psoriasis undergoes remission following loss of innervation, nerve function or nervous system injury, supports this hypothesis [69] . BoNT-A inhibits nerve-derived release of CGRP and SP, and this probably explains the subjective clinical observation of disease improvement in inverse psoriasis following BoNT-A administration by Zanchi et al [70] . Ward et al [69] demonstrated, using adult KC-Tie2 mouse (a murine model of psoriasiform dermatitis) that the intradermal injections of BoNT-A lead to a significant improvement versus placebo in acanthosis and a reduction of cutaneous lymphocyte infiltration.…”
Section: Psoriasismentioning
confidence: 99%
“…However, clinical reports and observational study published are few and not placebo-controlled. Zanchi et al [70] reported a good response to the BoNT-A treatment in 15 patients with inverse psoriasis, but the outcomes were evaluated with patient self-assessment (VAS scale for itch and pain) and a photographic evaluation of erythema and infiltration. For this reason, Chroni et al [71] raised several criticism in the study such as the absence of a quantitative measure in order to estimate the improvement (PASI score, for example) or a histological evaluation prior and post treatment.…”
Section: Psoriasismentioning
confidence: 99%